2020
DOI: 10.1785/0220190168
|View full text |Cite
|
Sign up to set email alerts
|

The 2016 Mw 5.9 Menyuan Earthquake in the Qilian Orogen, China: A Potentially Delayed Depth-Segmented Rupture Following from the 1986 Mw 6.0 Menyuan Earthquake

Abstract: An Mw 5.9 thrust earthquake occurred on 21 January 2016 in the northeastern Tibetan plateau, where another similar earthquake had ruptured in 1986. Because of the complexity and close proximity of multiple faults in this area, the exact causative fault sources for these two events have not previously been determined. We determined the seismogenic fault structural geometry of the 2016 event by analyzing the coseismic deformation from Sentinel-1A images, aftershock relocations, and geological data. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
4
14
0
Order By: Relevance
“…The moment is 1.121 × 10 18 Nm (shear modulus 30 GPa, M w 5.97), slightly larger than the magnitude reported by the GCMT catalog ( M w 5.9). The derived slip distribution shows good data fitting between simulations and InSAR observations (Figure S2 in Supporting Information ) and is in line with previous InSAR studies (e.g., Li et al., 2016; Liu et al., 2018; Wang et al., 2017; Xiong et al., 2019; Zhang et al., 2020).…”
Section: Fault Slip Distribution Modelsupporting
confidence: 89%
See 2 more Smart Citations
“…The moment is 1.121 × 10 18 Nm (shear modulus 30 GPa, M w 5.97), slightly larger than the magnitude reported by the GCMT catalog ( M w 5.9). The derived slip distribution shows good data fitting between simulations and InSAR observations (Figure S2 in Supporting Information ) and is in line with previous InSAR studies (e.g., Li et al., 2016; Liu et al., 2018; Wang et al., 2017; Xiong et al., 2019; Zhang et al., 2020).…”
Section: Fault Slip Distribution Modelsupporting
confidence: 89%
“…Given the simple surface deformation produced by the 2016 M w 5.9 earthquake (Figure 2a–2b and 2g–2h), a single plane is adequate to model its fault geometry, as shown in their small residues with single‐peak posterior probability distributions (Figures S1 and S2 in Supporting Information ). The optimal model indicates a thrust‐slip mechanism on a low‐angle, south‐dipping fault plane (strike = 122°, dip = 43°), similar to the source models from previous InSAR studies (e.g., Li et al., 2016; Liu et al., 2018; Wang et al., 2017; Xiong et al., 2019; Zhang et al., 2020).…”
Section: Coseismic Deformation and Fault Geometrysupporting
confidence: 74%
See 1 more Smart Citation
“…However, considering that the fault patch that slipped during the earthquake was only 20 km long (Y. Li, Shan, et al., 2016; H. Wang et al., 2017), yet the high‐strain segment is three times longer indicates that the earthquake might have induced postseismic creep. The Menyuan Earthquake was a thrust earthquake that occurred on a fault splay attached to the Haiyuan Fault at a depth of 10 km (Y. Li, Jiang, et al., 2016; H. Wang et al., 2017; Y. Zhang et al., 2020). The motion of the pop‐up structure might have released normal stress on the Lenglengling Fault thus making stress conditions conducive to creep on the Haiyuan Fault.…”
Section: Main Features In the Velocity And Strain‐rate Fieldsmentioning
confidence: 99%
“…Aftershocks relocation and earthquake rupture modeling studies revealed that this earthquake ruptured both eastern and western portions of TLSF and LLLF, respectively (Feng et al., 2022; Han, 2022; He et al., 2022; Liu, Zhuang, et al., 2022; Luo & Wang, 2022; LÜ et al., 2022; Peng et al., 2022; Xu et al., 2022; Zhu et al., 2022). The 2022 Menyuan earthquake is located approximately 30–40 km west to another two earlier Menyuan earthquakes (the 2016 Mw 5.9 and 1986 Mw 6.0 thrust earthquakes in the north LLLF and Minyue‐Damaying fault, respectively) (Peng et al., 2022; Yang et al., 2022; Zhang et al., 2020) (Figure 1). Peng et al.…”
Section: Introductionmentioning
confidence: 99%